Physiological- and performance-related effects of acute olive oil supplementation at moderate exercise intensity - Laura Esquius; Sergi Garcia-Retortillo; Natàlia Balagué; Robert Hristovski; Casimiro Javierre (Taylor & Francis Group, 2019)
Background The consumption of olive oil is associated with a diminished risk of cardiovascular disorders and mortality, but the impact of olive oil supplementation on endurance performance is still unclear. Since the beneficial effects of olive oil are observed at a systemic level, its effectiveness may not be precisely measured through the commonly registered maximal and threshold values of some physiological and performance parameters. In contrast, we suggest evaluating it through variables able to capture the coordinated behaviour of physiological systems. Thus, the aim of the current research was to assess the effect of an acute extra virgin olive oil supplementation on cardiorespiratory coordination (CRC) and performance, compared to palm oil. Methods Three separate effort test sessions were carried out separated by 7-day interval. During each session, participants (n = 7) repeated the same progressive and maximal walking test, but under different dietary supplementations in a randomized order: (1) olive oil, (2) palm oil, and (3) placebo. A principal component (PC) analysis of selected cardiovascular and cardiorespiratory variables was carried out to evaluate CRC. Eigenvalues of the first PC (PC1) and the loadings of the cardiorespiratory variables onto PC1 were compared among dietary supplementations. In order to more accurately evaluate CRC, all the tests were divided into 3 equal sections, corresponding to low, moderate, and high exercise intensities, and the aforementioned procedure was repeated for each section in all the tests. Results Statistically significant differences were observed regarding PC1 eigenvalues among dietary supplementations (χ 2 (8,2) = 6.3; p = .04), only at moderate intensity exercise. Specifically, PC1 eigenvalues were higher under olive oil compared to palm oil (2.63 ± 0.51 vs. 2.30 ± 0.28; Z = 2.03; p = .04; d = 0.80) and placebo supplementations (2.63 ± 0.51 vs. 2.38 ± 0.36; Z = 2.20; p = .03; d = 0.57). Conclusions Supplementation with extra virgin olive oil increased CRC during a progressive walking test at moderate intensity, although did not change performance and other physiological markers. CRC analysis appears as a sensitive tool to investigate the physiological and performance effects of dietary supplementations.